Effect of Resistance Training on Microvascular Density and eNOS Content in Skeletal Muscle of Sedentary Men. (November 2014) - Cocks, Matthew; Shaw, Christopher S.; Shepherd, Sam O.; Fisher, James P.; Ranasinghe, Aaron M.; Barker, Thomas A.; Tipton, Kevin D.; Wagenmakers, Anton J. M.
Abstract Objective The effects of RT on muscle mass, strength, and insulin sensitivity are well established, but the underlying mechanisms are only partially understood. The main aim of this study was to investigate whether RT induces changes in endothelial enzymes of the muscle microvasculature, which would increase NO bioavailability and could contribute to improved insulin sensitivity. Methods Eight previously sedentary males (age 20 ± 0.4 years, BMI 24.5 ± 0.9 kg/m2) completed six weeks of RT 3x/week. Muscle biopsies were taken from the m. vastus lateralis and microvascular density; and endothelial‐specific eNOS content, eNOS Ser1177 phosphorylation, and NOX2 content were assessed pre‐ and post‐RT using quantitative immunofluorescence microscopy. Whole‐body insulin sensitivity (measured as Matsuda Index), microvascular Kf (functional measure of the total available endothelial surface area), and arterial stiffness (AIx, central, and pPWV) were also measured. Results Measures of microvascular density, microvascular Kf, microvascular eNOS content, basal eNOS phosphorylation, and endothelial NOX2 content did not change from pre‐RT to post‐RT. RT increased insulin sensitivity (p < 0.05) and reduced resting blood pressure and AIx (p < 0.05), but did not change central or pPWV. Conclusions RT did not change any measure of muscle microvascular structure or function.